Local calibration review of AASHTOWare flexible pavement mechanistic empirical design software for Kansas - Saleh, Noura Sultan Hassan Mahmoud (Kansas State University, 2023)
Multiple state highway authorities have been pursuing the adoption of the latest AASHTOWare Pavement Mechanistic-Empirical Design (PMED). The PMED design guide utilizes theories of mechanics to predict pavement stress and strain responses using transfer functions to convert these responses to pavement distresses. These functions must be calibrated to local conditions for an accurate pavement performance prediction and subsequent design analysis. Previously, there were some efforts on local calibration of flexible pavement distress models in Kansas using AASHTOWare PMED versions 2.2.0 and 2.5.0 However, these calibration factors should be checked over time in accordance with updated software versions. The local calibration factors were evaluated using the newest version of AASHTOWare 2.6.2.2 Twenty-one actual constructed flexible pavements were selected for reviewing the local calibration factors for different distress models, including rutting, fatigue cracking, transverse cracking, and international roughness index (IRI). Statistical analysis was done for all the distresses to check the validity of these calibration factors on the latest AASHTOWare version 2.6.2.2. The new version showed a successful response using global and local calibration factors for rutting distress and IRI. However, top-down fatigue cracking distress function was drastically changed in PMED version 2.6.2.2 and new parameter inputs have been added to the model.
Keywords: AASHTOWare; Calibration; MEPDG; Pavement; Flexible